Comparison of efficiency and safety of open surgery, hybrid surgery and endovascular repair for the treatment of thoracoabdominal aneurysms: a systemic review and network meta-analysis - Liu, Tinghua; Zhao, Jiani; Sun, Jinjian; Wu, Kemin; Wang, Wei (Frontiers in Cardiovascular Medicine, 2023)
Objective The objective of this study was to perform a network meta-analysis (NMA) to assess the efficacy and safety of three different surgical interventions- open surgical repair (OSR), hybrid surgical repair (HSR), and endovascular repair (EVAR)- for the treatment of thoracoabdominal aortic aneurysms (TAAAs). Methods Electronic repositories like PubMed, Embase, Web of Science, Scopus, ScienceDirect, the Cochrane library, Clinical trial, and China National Knowledge Infrastructure (CNKI) were systematically searched to identify studies that compared the efficacy of OSR, HSR, and EVAR with endografts for the treatment of TAAAs until December 24th, 2022. Random-effects and fixed-effects models were employed to analyze the data gathered in a network meta-analysis. The study's primary outcomes of interest encompassed in-hospital mortality, long-term survival rate, and postoperative complications. Results Eleven comparative studies meet inclusion criterias. There were 2,222 patients in OSR, 1,574 patients in EVAR and 537 patients in HSR. EVAR has lower one-month mortality than OSR (RR: 0.31; 95% CI: 0.17–0.70) and HSR (RR: 0.37; 95% CI: 0.22–0.71), and lower incident rate of renal complications than HSR (RR: 0.20; 95% CI: 0.08–0.43) and OSR (RR: 0.34; 95% CI: 0.16–0.65). Nonetheless, there was no noteworthy discrepancy identified in the long-term survival rates of these procedures. Conclusions As compared with OSR, HSR, and EVAR, EVER has lower one-month mortality, and lower incident rates of complications. Systematic review registration PROSPERO (CRD42022313829).